What Must Pro‐Lifers Believe About the Moral Status of Embryos?. (12th March 2020) - Hershenov, David B.
Abstract: Embryo rescue cases and minimal miscarriage prevention research have been interpreted as showing that even pro‐lifers are not really committed to the unborn having the same moral status as the born. I will suggest instead that judgments about embryo rescues are often distorted by triage considerations that reveal nothing about differences in moral status between those saved and those not. I will present metaphysical and ethical considerations – none assuming a difference in moral status – why preventing millions of miscarriages does not warrant the massive redistribution of research funds that would occur to prevent the deaths of equal numbers of humans already born.